40 HADITS PEDOMAN NU KARYA KH. HASYIM ASYíARI Studi Takhrij dan Analisis Konteks Sosial Keagamaan Berdirinya NU - Hasan Suíaidi (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2014)
This study seeks to uncover the quality of 40 hadith on NU foundations, the religious and social background of their writing and selection, and the classification of themes contained in the book Arbaíina Haditsan Tataíallaqu bi Mabadiíi Nahdlat al-Ulamaí. This study revealed that the quality of the hadith varies between shaheeh, hasan, and dhaif. The themes range from da'wah/commanding the good and forbidding the evil, leadership, worship, adherence to the Sunnah, morality, and unity. Meanwhile, the religious and social context was influenced by both global and local situations.